2019
DOI: 10.3390/ijms20020411
|View full text |Cite
|
Sign up to set email alerts
|

Ceramide and Regulation of Vascular Tone

Abstract: In addition to playing a role as a structural component of cellular membranes, ceramide is now clearly recognized as a bioactive lipid implicated in a variety of physiological functions. This review aims to provide updated information on the role of ceramide in the regulation of vascular tone. Ceramide may induce vasodilator or vasoconstrictor effects by interacting with several signaling pathways in endothelial and smooth muscle cells. There is a clear, albeit complex, interaction between ceramide and redox s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 192 publications
(326 reference statements)
0
48
1
Order By: Relevance
“…5,17,[31][32][33] In a murine model of ceramide synthase 2 haploinsufficiency, a reduction in levels of very long-chain (C22:0 and C24:0) ceramides and a compensatory increase in levels of longchain ceramides (C16:0) was noted, resulting in an increased susceptibility to insulin resistance and hepatocyte apoptosis. 30 Given the role of ceramides in pancreatic b-cell dysfunction, insulin resistance and vascular reactivity, 34 increased cardiometabolic risk could potentially mediate the association with dementia. Indeed, we observed that higher levels of ceramides C24:0 and C22:0 relative to C16:0 were associated with a lower burden of white matter disease on MRI brain.…”
Section: Discussionmentioning
confidence: 99%
“…5,17,[31][32][33] In a murine model of ceramide synthase 2 haploinsufficiency, a reduction in levels of very long-chain (C22:0 and C24:0) ceramides and a compensatory increase in levels of longchain ceramides (C16:0) was noted, resulting in an increased susceptibility to insulin resistance and hepatocyte apoptosis. 30 Given the role of ceramides in pancreatic b-cell dysfunction, insulin resistance and vascular reactivity, 34 increased cardiometabolic risk could potentially mediate the association with dementia. Indeed, we observed that higher levels of ceramides C24:0 and C22:0 relative to C16:0 were associated with a lower burden of white matter disease on MRI brain.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we found several ceramides and SM (d34:1) were increased in age-related CSVD. Ceramides may cause endothelial dysfunction and increase the permeability of the blood-brain barrier by promoting oxidative stress, inflammation and reducing the production of nitric oxide [29][30][31], thus leading to CSVD [32]. Ceramides and sphingomyelins are components of myelin sheath in white matter, playing important roles in maintaining normal function of the myelin sheath [33].…”
Section: Age-related Csvdmentioning
confidence: 99%
“…In recent years, ceramides, a subgroup of sphingolipids, have received increased attention for their role in myriad pathophysiologic mechanisms, including those underlying cancer ( 23 25 ), inflammation ( 26 ), depression ( 27 ), and neurodegenerative disorders ( 28 ). Additionally, more recent studies have highlighted their increasingly important role in obesity and diabetes ( 9 , 29 31 ) as well as cardiovascular disease (CVD) ( 32 ). Preventing aberrant ceramide deposition can prevent or ameliorate a variety of cardiometabolic pathologies, including insulin resistance, CVD (atherosclerosis, heart failure), and hepatic steatosis ( 33 , 34 ), as well as mitochondrial dysfunction ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%